Ανίχνευση και ταυτοποίηση μικροοργανισμών από το σύστημα διανομής πόσιμου νερού της Λεμεσού και από εμφιαλωμένα νερά - Παρπούνα, Χριστιάνα (Τμήμα Γεωπονικών Επιστημών,Βιοτεχνολογίας και Τεχνολογίας Τροφίμων,Σχολή Γεωτεχνικών Επιστημών και Διαχείρισης Περιβάλλοντος, Τεχνολογικό Πανεπιστήμιο Κύπρου, 2012)
Microorganisms can survive and multiply in a Drinking Water Distribution System (DWDS) due to the presence of organic and inorganic nutrients and can be detected in plactonic form or in multilayer biofilms. This can result to contaminated water reaching the consumers’ taps despite disinfection at treatment points. During this study, samples were taken from households at different locations in the grater area of Limassol and also from bottled water available in the market. All samples were microbiologically tested following the ISO methods according to the directive 98/83/EC of the European Union. From a total of 24 samples from the DWDS, 21 (87,5%) were contaminated with one or more microorganisms belonging to the genera of Pseudomonas, Enterococcus, Acinetobacter, Bacillus, Aeromonas, Staphylococcus, Corynebacterium and Delftia. Following the analysis of the 18 different samples of bottled water 6 (33%), were contaminated with the 16S rDNA molecular identification revealing the presence of at least one of Acinetobacter johnsonii, Pseudomonas putida and Pseudomonas fluorescens. However, all samples tested both from the DWDS and bottled water, were free from E. coli. Access to safe and clean water is a fundamental human right and further research should focus on the quality of water in an attempt to prevent and reduce the prevalence of waterborne diseases.
Keywords: Microorganism; Water; Μικροοργανισμός; Νερό